Targeting USP11 may alleviate radiation-induced pulmonary fibrosis by regulating endothelium tight junction. (2nd January 2022) - Tang, Yiting; Yuan, Qian; Zhao, Congzhao; Xu, Ying; Zhang, Qi; Wang, Lili; Sun, Zhiqiang; Cao, Jianping; Luo, Judong; Jiao, Yang
Abstract: Purpose: Radiation-induced pulmonary fibrosis (RIPF) is a major side effect after radiotherapy for thoracic malignancies. However, rare anti-RIPF therapeutics show definitive effects for treating this disease. Ubiquitin-specific peptidase 11 (USP11) has been reported to promote transforming growth factor β (TGFβ) signaling which plays an essential role underlying RIPF. Herein, we explored the role of USP11 on RIPF. Materials and methods: In the present study, USP11-knockout ( Usp11 -/- ) mice were used to explore the effects of USP11 on RIPF. The lung tissue was obtained after receiving 30 Gy X-ray irradiation. The expression of USP11, TGF-β1, and a-SMA was determined by immunohistochemical and Western Blot, respectively. γ-H2 AX foci and TUNEL positive cells were detected by fluorescent technique to assess DNA damage and apoptosis. High-throughput proteomic analysis was applied to further explore the related mechanisms. The transwell co-culture method was used to investigate bystander effects in HELF cells induced by irradiated HMEC-1 cells in vitro . Results: Here we found that radiation activated USP11 in vivo and in vitro . Our results showed that USP11 deficiency effectively decreased serum TGF-β1 level, suppressed α-SMA expression, and mitigated pulmonary fibrosis. In addition, fewer γ-H2 AX foci and decreased apoptotic cells were identified after irradiation in the primary cells isolated from the lungs of Usp11 -/- mice. High-throughput proteomics analysis results showed that 22-upregulated and 158-downregulated proteins were identified in the lung tissues of Usp11 -/- mice after irradiation. Furthermore, gene set enrichment analysis (GSEA) revealed that USP11 deficiency affects the tight junction signaling pathway. Conclusions: We verified that USP11 deficiency remarkably reinforced tight junction in the endothelial cells and alleviated TGF-β1 to inhibit fibrosis of fibroblast cells. The present study preliminarily showed that USP11-knockout mitigated RIPF via reinforcement endothelial barrier function.